The impact of supervisor–subordinate racial-ethnic and gender dissimilarity on mentoring quality and turnover intentions: do positive affectivity and communal culture matter?. Issue 22 (16th December 2019) - Richard, Orlando C.; McKay, Patrick F.; Garg, Sargam; Pustovit, Sasha
Abstract: Demographic dissimilarity in supervisor–subordinate dyads is often associated with negative subordinate work experiences. Extending relational demography and mentoring research, the authors examined whether employee positive affectivity and communal culture ameliorated the negative effects of supervisor–subordinate racial (gender) dissimilarity on mentoring quality and reduced turnover intentions. Within a sample of 197 employees from various U.S. companies, racial dissimilarity was negatively related to mentoring quality and this relationship was stronger among employees who were lower in positive affectivity. Finally, mentoring quality mediated the racial dissimilarity–turnover intentions relationship, as moderated by positive affectivity. Specifically, racial dissimilarity reduced mentoring quality, thereby increasing turnover intentions, especially for employees who were low in positive affectivity. The research and practical implications of the study findings are noted.